The Interplay Between Safety Leadership and Construction Workers’ Safety Behavior: Do Perceived Employer Safety Obligations Matter? - Marwan Elosta; Ahmad Alzubi (Buildings)
In an industry where safety is paramount yet frequently compromised, the transformative impact of safety leadership on workers’ safety behavior illuminates a path to reducing construction hazards and fostering a culture of proactive safety practices. Combining transformational leadership theory, social exchange theory, and the theory of planned behavior, this research examines the complex interplay between safety leadership and safety behavior through the mediating role of safety knowledge, specifically investigating how perceived employer safety obligations moderate these relations. Based on 359 cross-sectional data obtained from construction industry professionals in Istanbul, Turkey, it was found that safety leadership significantly boosts safety behavior and safety knowledge, with safety knowledge serving as an effective mediator. Although perceived employer safety obligations did not moderate the affect the safety leadership on safety knowledge, they significantly moderated the link between safety leadership and safety behavior, as well as between safety knowledge and safety behavior, emphasizing the crucial role of perceived employer safety obligations in enhancing safety practices and outcomes. This study substantially enhances the construction safety management literature by elucidating the intricate dynamics between safety leadership and safety behavior and the pivotal role of perceived employer safety obligations. It offers robust theoretical advancements and practical strategies, enabling construction firms to leverage safety leadership for improved workplace safety outcomes and organizational performance.